Buckling and Post-buckling Performance of Advanced Composite Stiffened Panel Under Compression - ZHANG Haoyu; HE Yuting; FENG Yu; TAN Xiangfei; ZHENG Jie (Journal of Aeronautical Materials, 2016)
The axial compressive experiment was conducted on the domestic advanced composite stiffened panel, and its buckling and post-buckling performance was analyzed by monitoring strain and out-of-plane displacement of typical positions. The initial buckling load and buckling mode of panels were calculated by engineering methods to direct the follow-up axial compressive experiment. The experimental results show that the buckling patterns are mainly local buckling of panels between stiffeners, the second buckling of few positions of panels and cylindrical buckling of all 4 stiffeners successively; after local buckling of panels, part of load bearded by panels before is transferred to stiffeners and then stiffeners become the main bearing part; after fracture failure of stiffeners, the specimen is destroyed rapidly; the average value of failure load is 482.67 kN, which is 2.37 times of 204 kN of the average value of buckling load; the composite stiffened panel can bear more load after buckling.